Effects of Wood Hydraulic Properties on Water Use and Productivity of Tropical Rainforest Trees - Kotowska, Martyna M.; Link, Roman M.; Röll, Alexander; Hertel, Dietrich; Hölscher, Dirk; Waite, Pierre-André; Moser, Gerald; Tjoa, Aiyen; Leuschner, Christoph; Schuldt, Bernhard (Frontiers in Forests and Global Change, 2021)
The efficiency of the water transport system in trees sets physical limits to their productivity and water use. Although the coordination of carbon assimilation and hydraulic functions has long been documented, the mutual inter-relationships between wood anatomy, water use and productivity have not yet been jointly addressed in comprehensive field studies. Based on observational data from 99 Indonesian rainforest tree species from 37 families across 22 plots, we analysed how wood anatomy and sap flux density relate to tree size and wood density, and tested their combined influence on aboveground biomass increment (ABI) and daily water use (DWU). Results from pairwise correlations were compared to the outcome of a structural equation model (SEM). Across species, we found a strong positive correlation between ABI and DWU. Wood hydraulic anatomy was more closely related to these indicators of plant performance than wood density. According to the SEM, the common effect of average tree size and sap flux density on the average stem increment and water use of a species was sufficient to fully explain the observed correlation between these variables. Notably, after controlling for average size, only a relatively small indirect effect of wood properties on stem increment and water use remained that was mediated by sap flux density, which was significantly higher for species with lighter and hydraulically more efficient wood. We conclude that wood hydraulic traits are mechanistically linked to water use and productivity via their influence on sap flow, but large parts of these commonly observed positive relationships can be attributed to confounding size effects.